Effect of superstimulatory treatments on the expression of genes related to ovulatory capacity, oocyte competence and embryo development in cattle. - Barros, Ciro M; Satrapa, Rafael A; Castilho, Anthony C S; Fontes, Patrícia K; Razza, Eduardo M; Ereno, Ronaldo L; Nogueira, Marcelo F G (CSIRO Publishing, 2012)
Multiple ovulation (superovulation) and embryo transfer has been used extensively in cattle. In the past decade, superstimulatory treatment protocols that synchronise follicle growth and ovulation, allowing for improved donor management and fixed-time AI (FTAI), have been developed for zebu (Bos indicus) and European (Bos taurus) breeds of cattle. There is evidence that additional stimulus with LH (through the administration of exogenous LH or equine chorionic gonadotrophin (eCG)) on the last day of the superstimulatory treatment protocol, called the 'P-36 protocol' for FTAI, can increase embryo yield compared with conventional protocols that are based on the detection of oestrus. However, inconsistent results with the use of hormones that stimulate LH receptors (LHR) have prompted further studies on the roles of LH and its receptors in ovulatory capacity (acquisition of LHR in granulosa cells), oocyte competence and embryo quality in superstimulated cattle. Recent experiments have shown that superstimulation with FSH increases mRNA expression of LHR and angiotensin AT(2) receptors in granulosa cells of follicles >8 mm in diameter. In addition, FSH decreases mRNA expression of growth differentiation factor 9 (GDF9) and bone morphogenetic protein 15 (BMP15) in oocytes, but increases the expression of both in cumulus cells, without diminishing the capacity of cumulus-oocyte complexes to generate blastocysts. Although these results indicate that superstimulation with FSH is not detrimental to oocyte competence, supplementary studies are warranted to investigate the effects of superstimulation on embryo quality and viability. In addition, experiments comparing the cellular and/or molecular effects of adding eCG to the P-36 treatment protocol are being conducted to elucidate the effects of superstimulatory protocols on the yield of viable embryos.
Keywords: gonadorelin; animal; animal disease; artificial insemination; cattle; cumulus cell; drug effect; embryo development; estrus cycle; female; gene expression regulation; growth, development and aging; metabolism; oocyte; ovary; ovulation; ovulation induction; physiology; pregnancy; prenatal development; Animals; Cattle; Cumulus Cells; Embryonic Development; Estrus Synchronization; Female; Gene Expression Regulation, Developmental; Gonadotropin-Releasing Hormone; Insemination, Artificial; Oocytes; Ovary; Ovulation; Ovulation Induction; Pregnancy